The Effect of Intrinsic and Extrinsic Motivation on Civil Servants' Job Satisfaction Through Services at the Patumbak District Office - Yomilia Hulu; Boby Indra Prayoga; Cut Sah Kha Mei Zsazsa (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Job satisfaction is a crucial factor in supporting the effectiveness of public sector organizations, particularly at the sub-district government level that directly serves the community. Work motivation, both intrinsic and extrinsic, greatly influences employee satisfaction; however, the quality of public services can determine the strength of that relationship. Therefore, this study is important to examine how service quality strengthens the influence of motivation on employee job satisfaction. The study aims to determine the effect of intrinsic and extrinsic motivation on job satisfaction with service quality as a mediating variable. This research used a quantitative method with an associative approach. Data were collected through questionnaires distributed to 31 respondents who are employees at the Patumbak Sub-District Office. Data analysis techniques include validity tests, reliability tests, classical assumption tests, t-tests, F-tests, coefficient of determination (R²), and path analysis using SPSS version 25. The results indicate that both intrinsic and extrinsic motivation have a positive and significant effect on service quality and job satisfaction. Service quality also significantly influences job satisfaction. The direct influence of extrinsic motivation on job satisfaction is greater than its indirect effect through service quality, while for intrinsic motivation, the opposite is true. This indicates that service quality serves as a partial mediating variable. In conclusion, employee job satisfaction at the Patumbak Sub-District Office is influenced not only by external factors such as rewards and social recognition, but also by internal motivation and the quality of service delivered professionally and efficiently.